2008
DOI: 10.1093/rheumatology/ken317
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline in the treatment of fibromyalgia: a systematic review of its efficacy

Abstract: The objective of this study was to assess the efficacy and safety of amitriptyline as a treatment of FM. A comprehensive computerized search in Medline (Pubmed), EMBASE and The Cochrane Library was performed. Randomized controlled trials (RCTs) comparing amitriptyline vs placebo in adult patients suffering from FM were identified, the methodological quality was assessed and the results of the main outcomes were evaluated. Ten RCTs were identified. Large clinical variability and statistical heterogeneity preclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 28 publications
1
36
0
1
Order By: Relevance
“…There was no difference in discontinuation rates compared with patients receiving placebo. Nishishinya et al 13 in their high-quality review concluded that 25 mg/day improved pain, sleep and fatigue at 6–8 weeks of treatment but not at 12 weeks while 50 mg/day did not demonstrate efficacy. Amitriptyline evaluation: w eak for, at low dose (100% agreement) .…”
Section: Resultsmentioning
confidence: 99%
“…There was no difference in discontinuation rates compared with patients receiving placebo. Nishishinya et al 13 in their high-quality review concluded that 25 mg/day improved pain, sleep and fatigue at 6–8 weeks of treatment but not at 12 weeks while 50 mg/day did not demonstrate efficacy. Amitriptyline evaluation: w eak for, at low dose (100% agreement) .…”
Section: Resultsmentioning
confidence: 99%
“…With the presence of a comorbid sleep disorder, or any other concurrent psychological disorder, pharmacotherapeutic interventions should be implemented that avoid prescribing the patient more medications than clinically necessary (i.e., poly-pharmacy). For example, according to (12), choosing a sedating antidepressant or an atypical antidepressant may alleviate neuropathic pain, reduce depression and anxiety symptoms, and may induce sleep onset. This will reduce interactions and longterm side effects from poly-pharmacy.…”
Section: Rethinking the Psychogenic Model Of Crpsmentioning
confidence: 99%
“…With regard to the treatment of fibromylagia with associated fatigue, there is a more comprehensive body of data supporting the utility of TCA. In six RCTs in fibromyalgia patients, amitriptyline 25 mg/day demonstrated therapeutic superiority to placebo on symptoms of pain, sleep, and fatigue at 6 -8 weeks, although the benefit appeared to wane at 12 weeks [41,42]. However, whether these findings could be extended to patients with CFS is questionable.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%